A Novel Combination of Homeobox Genes Is Expressed in Mesenchymal Chorionic Stem/Stromal Cells in First Trimester and Term Pregnancies. (November 2014) - Liu, Haiying; Murthi, Padma; Qin, Sharon; Kusuma, Gina D.; Borg, Anthony J.; Knöfler, Martin; Haslinger, Peter; Manuelpillai, Ursula; Pertile, Mark D.; Abumaree, Mohamed; Kalionis, Bill
Human chorionic mesenchymal stem/stromal cells (CMSCs) derived from the placenta are similar to adult tissue-derived MSCs. The aim of this study was to investigate the role of these cells in normal placental development. Transcription factors, particularly members of the homeobox gene family, play crucial roles in maintaining stem cell proliferation and lineage specification in embryonic tissues. In adult tissues and organs, stem cells proliferate at low levels in their niche until they receive cues from the microenvironment to differentiate. The homeobox genes that are expressed in the CMSC niche in placental tissues have not been identified. We used the novel strategy of laser capture microdissection to isolate the stromal component of first trimester villi and excluded the cytotrophoblast and syncytiotrophoblast layers that comprise the outer layer of the chorionic villi. Microarray analysis was then used to screen for homeobox genes in the microdissected tissue. Candidate homeobox genes were selected for further RNA analysis. Immunohistochemistry of candidate genes in first trimester placental villous stromal tissue revealed homeobox genes Meis1, myeloid ectropic viral integration site 1 homolog 2 ( MEIS2 ), H2.0-like Drosophila ( HLX ), transforming growth factor β-induced factor ( TGIF ), and distal-less homeobox 5 ( DLX5 ) were expressed in the vascular niche where CMSCs have been shown to reside. Expression of MEIS2, HLX, TGIF, and DLX5 was also detected in scattered stromal cells. Real-time polymerase chain reaction and immunocytochemistry verified expression of MEIS2, HLX, TGIF, and DLX5 homeobox genes in first trimester and term CMSCs. These data suggest a combination of regulatory homeobox genes is expressed in CMSCs from early placental development to term, which may be required for stem cell proliferation and differentiation.